The outlandish adventures of Liberty Aimes - Easton, Kelly (Wendy Lamb Books, 2009)
Ten-year-old Libby Aimes escapes her prison-like home by using a strange concoction of her father's, then tries to make her way to the boarding school of her dreams, aided by various people and animals.